Crashworthiness analysis of ellptical automative side door beam for lightweight design - Rasooliyazdi, Ehsan (2014)
Side door beam (SDB) is one of the most important components in a vehicle to protect the passengers from the side impact. Side impact is the second type of common accident after frontal impact. The limited physical space between the car body and the occupants lead to severe injury due to high deformation of the car body. The weight reduction and crashworthiness improvement of the SDB are two problems that must be solved. In this study, the main objective is to optimize the crashworthiness behavior of different SDBs under impact test. Reducing the weight of SDB as well as the maximum impact load are two significant targets which are investigated simultaneously. In this respect, the specific energy absorption (SEA) and the peak load (PL) are two parameters which play the role key to develop the aforementioned goals. To investigate the crashworthiness of an SDB, two cross- sectional configurations of SDB which are elliptical and rectangular are selected. Three material alloys of magnesium, aluminum and steel as a reference material are assigned to the elliptical and rectangular SDB. In addition, these simulations are conducted with three orientation angles which are 0,45 and 90 degree with respect to the rigid wall impactor. For each case of studies, the elliptical and rectangular cross section of the SDB under each orientation angle is taken into account by considering two variables of geometrical parameters; thickness for both design beam and minor to major radii ratio for elliptical and ratio of sizes for rectangular shape. All the aforementioned steps are performed by LS-DYNA software which are used widely for impact problems. The multi-objective optimization framework is used to find the optimum geometrical characteristics in each series of simulations. Consequently, the optimization process of the SDB is performed using response surface method (RSM) in terms of the weight average method and the geometrical average method. The series of results are presented in a Pareto Frontier graph to show a group of solutions with optimal points and to meet both mentioned objectives at the same time. The optimization steps are performed by MATLAB software. The results show magnesium alloy has good ability to absorb more energy compare with the aluminium and steel alloys. On the other hand, elliptical cross section cause to lower PL respect to rectangular design. Also, the orientation angle of 90 degrees lead to decrease the PL compare with the 0 and 45 degree. Consequently, elliptical SDB made by magnesium material with the angle of 90 degrees with respect to the rigid wall became the best solution in order to achieve the highest energy absorption (SEA) and the lowest peak load (PL). The selected SDB is optimized to get the optimal design which shows it has 0.5mm thickness and the ratio of radii is 0.284. The SEA and PL of optimized SDB are equal to 1203.74 (J/Kg) and 8.477 (KN) respectively.